2012
DOI: 10.1007/s00381-012-1977-4
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial intraventricular solitary schwannoma. Case report and literature review

Abstract: The literature describes less than 45 cases of schwannomas not associated to cranial nerves of the following locations: intramedullary, leptomeningeal and only 12 intraventricular cases. The three theories explaining the origin of this last group describe: (1) a neoplastic transformation of peripheral nerve fibres, (2) a neoplastic transformation of autonomic neural tissue located within the intraventricular choroid plexus and (3) an abnormal embryogenesis leading to a failed migration of the neural crest cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…S-100 and vimentin are typically positively expressed, while GFAP and EMA are often negatively expressed ( 7 , 25 ). Through a literature review, we found that some cases appeared as misdiagnoses based on the preoperative and intraoperative frozen section, and the misdiagnoses included ependymoma, cystic astrocytoma, cystic meningioma, hemangioblastoma, fibroblastic meningioma, papilloma and choroid plexus carcinoma ( 8 , 14 , 16 , 18 , 21 , 27 ). In addition, the majority of the 23 cases were diagnosed as LVES based on the pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…S-100 and vimentin are typically positively expressed, while GFAP and EMA are often negatively expressed ( 7 , 25 ). Through a literature review, we found that some cases appeared as misdiagnoses based on the preoperative and intraoperative frozen section, and the misdiagnoses included ependymoma, cystic astrocytoma, cystic meningioma, hemangioblastoma, fibroblastic meningioma, papilloma and choroid plexus carcinoma ( 8 , 14 , 16 , 18 , 21 , 27 ). In addition, the majority of the 23 cases were diagnosed as LVES based on the pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…The final theory involves neoplastic transformation of pluripotent mesenchymal cells into Schwann cells after tissue injury. 9 No association between intraventricular schwannomas and genetic syndromes has been identified.…”
Section: Discussionmentioning
confidence: 99%